Pengaruh Sumber Inokulum dan Dosis pada Perbanyakan Fungi Mikoriza Arbuskula (FMA) dengan Tanaman Inang Jagung Manis (Zea mays saccharate, sturt) - Desvita, Desvita; Mahmud, Yudhi; Asad, Faisal Al; Dwimartina, Fina; Laila, Fadhillah (Jurnal Agro Wiralodra, 2024)
Arbuscular Mycorrhizal Fungi (FMA) are a type of mycorrhiza that is obligative, symbiotic that requires a host plant. Sweet corn plants are suitable plants to be used as host plants because of their greedy nature for nutrients. This study aims to determine the effect between mycorrhiza and different doses of FMA on the vegetative growth of sweet corn host plants and the highest number of spores with inoculum sources derived from mango plants. The research was carried out in the greenhouse of the Faculty of Agriculture and Science Laboratory, Wiralodra University in March – August 2023. The experimental design used in this study was a two-factor Randomized Group Design. The first factor is the source of inoculum consisting of S 1 = Source of Inoculum from Biotroph, S 2 = Source of Inoculum from Lobener Village, S 3 = Source of Inoculum from Jatisawit Village and S 4 = Source of Inoculum from Krasak Village. The second factor is the dose of FMA, which consists of: D1 = 20 grams / Polybag, D2 = 40 grams / polybag. The results showed that there was no interaction between inoculum source and FMA dose on spore count, FMA colonization, plant height, root length, root volume, dry root weight, fresh header weight and dry header weight. But it has a noticeable effect on the number of leaves. The best source of inoculum and FMA dose is shown by the treatment of S1 source of inoculum from Biotrop with a combination dose of Biotrope 20 grams / polybag and Biotrope 40 grams / polybag.